Evaluasi Program Sekolah Digital dalam Meningkatkan Pemanfaatan Teknologi untuk Pembelajaran - Febriani, Susanda; Zakir, Supratman; Ilmi, Darul; Setia Pramana, Roby (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The rapid development of technology in the 21st century has greatly affected education. In education, technology has become very important to support the teaching and learning process. Teachers play an important role in this, and they must have strong skills to make students want to learn. However, many teachers at SDN 03 Pakan Kurai still have difficulty using learning technology, which ultimately hinders the learning process. The focus of this descriptive qualitative research is how technology is used in learning in grade 5 of SDN 03 Pakan Kurai and how the digital school programme is assessed. This research uses the CIPP evaluation method with a descriptive qualitative approach oriented towards case studies. The results show that technology has been used well in learning overall. However, there are some major barriers. These include unstable internet networks, teachers' inability to use technology, and lack of variety in the use of learning applications. As a result, some students lack motivation to learn, which impacts on their learning outcomes.